Distribution Of Clinical Cases of Referral Patients for CBCT-3D Radiographic Examinations at RSKGMP Universitas Airlangga - Astuti, Eha Renwi; Savitri, Yunita; Putra, Ramadhan Hardani; Ramadhani, Nastiti Faradilla; Nurrachman, Aga Satria; Adiningsih, Adiningsih; Faikoh, Nur Laili Izzatul (Indonesian Dental Association, 2022)
Introduction: CBCT-3D (Cone Beam Computed Tomography) is an advanced radiographic imaging technology that is currently being developed and utilized in dentistry, with the advantages of accurately depicting three-dimensional (3D) tissue structures, minimal distortion, and low radiation dose. RSKGMP Universitas Airlangga is an educational dental hospital and one of the few hospitals in Surabaya city and also East Java Province that provides CBCT-3D examination services for various cases- thus becoming a referral center for the radiographic examination in the region. A lot of clinical case referrals have been recorded, but no one has researched the distribution of clinical cases referred for CBCT-3D examination. Objective: This study is aimed to determine the distribution of clinical cases referred for CBCT-3D radiographic examination at RSKGMP Universitas Airlangga based on origin, age, and gender. Methods: This study is a descriptive study with a sample of all clinical case medical records, CBCT-3D examination reference data at RSKGMP Universitas Airlangga from July 2015 to March 2020, which met the sample criteria. Furthermore, the data is tabulated and displayed using pie charts and bar charts. Results: Most referrals for CBCT-3D radiography came from internal referrals of RSKGMP Universitas Airlangga (78%). The elderly patients (46 years and over) had the most referrals (59%) of all age groups with the most indication for implant cases (78.9%). Female patients slightly more dominated the total referrals (57.5%) than male patients (42.5%). Conclusion: Most of the clinical cases of referral for CBCT-3D radiographic examination were implants and came from internal RSKGMP Universitas Airlangga, with the most referral age category being elderly and dominated by female patients.